Formigas, fogo e seus efeitos sobre os invasores de termiteiros - Ivan Menezes Monteiro (2015)
The invasion of social insect nests by opportunistic species is a frequently reported phenomenon. This behavior allows the attacker to enjoy the benefits provided by the nest without dealing with the burden of its construction. Among the organisms associated with termite mounds are ants, arachnids, insects, crustaceans, and millipedes. The eusocial behavior of ants allows the recruitment of various colony individuals to defend territories and resources. When associated to termite mounds, ants can act as an indirect protection of mounds, reducing the success of invasions. Another factor that can affect the rate of térmite mounds invasions is fire. Fire affects fauna mainly by eliminating individuals, and may or may not affect species richness. Indirectly, it also affects the availability of resources by reducing the density of the vegetation cover, which could lead to increased rates of invasions by organisms looking for food resources and shelter. The aim of this study was to test the hypotheses that: I - the presence of contiguous ant nests reduces the termites mounds invasion rate by other organisms and II térmites mounds exposed to fire have higher invasion rate. It was collected 30 termite mounds , 15 present on burned areas and 15 at unburned areas at PARNA Serra do Cipo in Minas Gerais. Among the sampled nests , 19 had associated anthills, 9 from burned areas and 10 from unburned areas. The termite mounds were removed and placed in plastic bags for transportation. In laboratory they were kept frozen until sorting of the content. The organisms founded were identified and quantified. To establish the effects of fire and the presence of anthills on termite nests, GLM 's were built where the occurrence of fire and the presence of anthills were the explanatory variables and the richness of invaders and inquilines the response variables. There was no significant response of fauna to the occurrence of fires (P> 0.05), indicating that termite mounds are safe places for fauna during fires. However , the presence of anthills reduced the invaders richness (P < 0.05), but did not affect the inquilines richness The invasion of social insect nests by opportunistic species is a frequently reported phenomenon. This behavior allows the attacker to enjoy the benefits provided by the nest without dealing with the burden of its construction. Among the organisms associated with termite mounds are ants, arachnids, insects, crustaceans, and millipedes. The eusocial behavior of ants allows the recruitment of various colony individuals to defend territories and resources. When associated to termite mounds, ants can act as an indirect protection of mounds, reducing the success of invasions. Another factor that can affect the rate of térmite mounds invasions is fire. Fire affects fauna mainly by eliminating individuals, and may or may not affect species richness. Indirectly, it also affects the availability of resources by reducing the density of the vegetation cover, which could lead to increased rates of invasions by organisms looking for food resources and shelter. The aim of this study was to test the hypotheses that: I - the presence of contiguous ant nests reduces the termites mounds invasion rate by other organisms and II térmites mounds exposed to fire have higher invasion rate. It was collected 30 termite mounds , 15 present on burned areas and 15 at unburned areas at PARNA Serra do Cipo in Minas Gerais. Among the sampled nests , 19 had associated anthills, 9 from burned areas and 10 from unburned areas. The termite mounds were removed and placed in plastic bags for transportation. In laboratory they were kept frozen until sorting of the content. The organisms founded were identified and quantified. To establish the effects of fire and the presence of anthills on termite nests, GLM 's were built where the occurrence of fire and the presence of anthills were the explanatory variables and the richness of invaders and inquilines the response variables. There was no significant response of fauna to the occurrence of fires (P> 0.05), indicating that termite mounds are safe places for fauna during fires. However , the presence of anthills reduced the invaders richness (P < 0.05), but did not affect the inquilines richness (P> 0.05) indicating that defensive postures of ants though inhibit the installation of invaders, are not directed against termites.(P> 0.05) indicating that defensive postures of ants though inhibit the installation of invaders, are not directed against termites.